2021
DOI: 10.1111/tpj.15367
|View full text |Cite
|
Sign up to set email alerts
|

At4g29530 is a phosphoethanolamine phosphatase homologous to PECP1 with a role in flowering time regulation

Abstract: SUMMARY Phosphatidylcholine (PC) and phosphatidylethanolamine (PE) are the most abundant phospholipids in membranes. The biosynthesis of phospholipids occurs mainly via the Kennedy pathway. Recent studies have shown that through this pathway, choline (Cho) moieties are synthesized through the methylation of phosphoethanolamine (PEtn) to phosphocholine (PCho) by phospho‐base N‐methyltransferase. In Arabidopsis thaliana, the phosphoethanolamine/phosphocholine phosphatase1 (PECP1) is described as an enzyme that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…For instance, each PECP protein demonstrates some ability to cleave PPi, even if only marginally. In fact, the pyrophosphatase activity measured in vitro for PECP2 was quite low (<1 nmol Pi min -1 mg protein -1 ; May et al, 2011) in comparison to the one associated with PECP3 (177 nmol Pi min -1 mg protein -1 ; Tannert et al, 2021), although another study only revealed a very marginal pyrophosphatase activity for PECP3 (Hasnain et al, 2016). Interestingly, their in vitro specific activities also suggested that each of these three enzymes metabolizes PEtn more efficiently than PCho in vitro (PECP1: 3,665 (PEtn) versus 475 (PCho) nmol Pi min -1 mg protein -1 (May et al, 2012); PECP2: 0.02 (PEtn) versus<0.001 (PCho) nmol Pi min -1 mg protein -1 (May et al, 2011); PECP3: 1,379 (PEtn) versus 315 (Pcho) nmol Pi min -1 mg protein -1 (Tannert et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…For instance, each PECP protein demonstrates some ability to cleave PPi, even if only marginally. In fact, the pyrophosphatase activity measured in vitro for PECP2 was quite low (<1 nmol Pi min -1 mg protein -1 ; May et al, 2011) in comparison to the one associated with PECP3 (177 nmol Pi min -1 mg protein -1 ; Tannert et al, 2021), although another study only revealed a very marginal pyrophosphatase activity for PECP3 (Hasnain et al, 2016). Interestingly, their in vitro specific activities also suggested that each of these three enzymes metabolizes PEtn more efficiently than PCho in vitro (PECP1: 3,665 (PEtn) versus 475 (PCho) nmol Pi min -1 mg protein -1 (May et al, 2012); PECP2: 0.02 (PEtn) versus<0.001 (PCho) nmol Pi min -1 mg protein -1 (May et al, 2011); PECP3: 1,379 (PEtn) versus 315 (Pcho) nmol Pi min -1 mg protein -1 (Tannert et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…This was already suggested following the characterization of hypocotyl elongation in pecp1/2/3 triple mutants and fugu5 pecp1/2 triple mutants (Hanchi et al, 2018), but we performed a more in-depth characterization of these mutants, along with the demonstration that fugu5 PPi homeostasis defects cannot be complemented by pecp2 overexpression. The initial in vitro characterization of PECP2 (May et al, 2011), completed later on by characterizing PECP1 and PECP3 (May et al, 2011;Hasnain et al, 2016;Tannert et al, 2021), remains fundamental for the study of the PECP family, as it clearly demonstrates that each of these enzymes can dephosphorylate a range of different substrates with different affinities. For instance, each PECP protein demonstrates some ability to cleave PPi, even if only marginally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, TH2 was shown to specifically catalyze this reaction and is reported to be found in mitochondria and the cytosol (Mimura et al., 2016) (Figure 1b). Plastid TMP phosphatases might also exist, but they have yet to be validated in vivo (Hasnain et al., 2016; Tannert et al., 2021). Pyrophosphorylation is catalyzed by two functionally redundant thiamine pyrophosphokinases (TPKs) that are localized to the cytosol in Arabidopsis (Ajjawi et al., 2007) (Figure 1b).…”
Section: The Vitamin B1 Familymentioning
confidence: 99%